Do Federal Reserve Bank presidents pursue regional or national interests? New evidence based on speeches - Bernd Hayo; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
In this paper, we analyze the determinants of speeches by Federal Reserve (Fed) officials over the period January 1998 to September 2009. Econometrically, we use a probit model with regional and national macroeconomic variables to explain the subjectively coded content of these speeches. Our results are, first, that Fed Governors and presidents follow a Taylor rule when expressing their opinions: a rise in expected inflation (unemployment) makes a hawkish speech more (less) likely. Second, the content of speeches by Fed presidents is affected by both regional and national macroeconomic variables. Third, speeches by nonvoting presidents are more focused on regional economic development than are those by voting presidents. Finally, voting presidents and Governors are less backward-looking in their wording than are nonvoting presidents.
Keywords: D72; E52; E58; 330; central bank communication; disagreement; Federal Reserve Bank; monetary policy; regional representation; speeches; Geldpolitik; Staatliche Information; Föderalismus; Regionale Entwicklung; USA